Mathematical modelling of a hydraulic accumulator for hydraulic hybrid drives. Issue 5 (2nd September 2016) - Pfeffer, A.; Glück, T.; Kemmetmüller, W.; Kugi, A.
ABSTRACT: Hydraulic accumulators are used as energy storages in a wide area of applications. In particular, in automotive hybrid drive-trains, this type of energy storage is an interesting alternative to today's common strategies like chemical batteries or flywheels. This article deals with the mathematical modelling of a hydraulic accumulator for passenger vehicles, which comprises a carbon fibre reinforced plastic (CFRP) body and aluminium piston. The thermodynamical behaviour of the oil and gas as well as the interaction with the CFRP body is investigated in detail. Starting from a complex model, two models of reduced complexity are derived. The validation of these models with measurement data from a test drive with a prototype series hydraulic hybrid drive-train proves their high accuracy.